Impact of Leadership Styles on Employee Performance in Micro-Finance Banking Sector: Evidence from Pakistan - Muhammad Zulqarnain; Zulqarnain Ali (Business and Applied Management Journal, 2023)
This study uses an empirical approach to examine the relationship between different Leadership styles and employee Performance in the microfinance banking sector. Here, we look at how seven distinct leadership styles (autocratic, democratic, laissez-faire, transformational, transactional, charismatic, servant, and situational leadership) affect employee performance in the workplace. With this information, executives can make better decisions that will help their organizations advance. The study is cross-sectional, meaning that data was collected at a particular, predefined point in time. Eleven microfinance institutions are spread out over Pakistan; from those, 192 participants are selected randomly to participate in the study. Data is collected through a self-administered questionnaire. Data are subjected to correlation and regression analysis and other descriptive and inferential statistical tests using IBM SPSS and Smart PLS 4. According to the results, CEOs in the microfinance banking sector would do well to embrace a situational leadership style like charismatic, democratic, servant, or transformational leadership. Employee leadership, Performance, workplace satisfaction, and organizational loyalty all improve when managers adopt these practices. However, research finds no correlation between autocratic, laissez-faire, or transactional leadership and employee performance, suggesting that these styles may be less successful at motivating employees. However, all other leadership styles benefit every organization in improving employee performance, especially in the banking sector.